Identifikasi perubahan suhu udara dan curah hujan di Bogor - Hidayat, Rahmat; Farihah, Alfi Wardah (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2020)
Climate datasets were analyzed to identify the changing climatic parameters and extreme events in Bogor, West Java. This study aims to analyze the characteristic of observational datasets in Baranangsiang and Dramaga, namely, air temperature and rainfall, and to indentify the changing structure of those climate parameters. The analysis has been conducted using RClimdex to understand the long-term changing air temperature and rainfall based on 10 indices for air temperature and 8 indices for rainfall. Results show that the rainfall in Baranangsiang has the daily mean of 10 mm/day and in Dramaga of 8 mm/day. The daily mean of air temperature in Baranangsiang and Dramaga is 27˚C and 25.5˚C, respectively. Generally, the declined slopes of the temperature indices in Barangsiang, namely, TN90p, TNx, TX10p, TNn, TXn, TR20, and SU25, indicate cooler temperature. In Dramaga, the increased temperature indices, namely, TN90p, TX90p, TXx, SU25, and TXn, indicate the warmer temperature. The rainfall indices generally decline, except for CDD, which indicate the increased consecutive dry days in Baranangsiang.